Contemporary performativities and the imperative of participation in digital technologies - Cánepa Koch, Gisela (2014)
In a processual perspective of social life, technology works within discursive and action frames that make it possible. these frames provide meaning and legitimate technology but are also produced through technology and its uses. In other words, actions frames of an era are constitutive of and constituted by technology. this perspective follows a performative approach on digital technologies which allow the authors to problematize them in terms of their actors, discourses, and practices. On this way, the authors go beyond views that tend to dichotomize in order to understand issues of representation and power relations. Yet, what happens when actor’s performances and the performative force of their practices are no longer an aspect of their dynamics and configuration, but rather a normative force? In other words, what is at stake when actors and their performances are organized by performance as a mandate, that is, as a regime of truth? In a context where the principles of efficiency, effectiveness and efficacy are a mandate, there is a need to ask this sort of question, particularly in relation to the paradoxes it poses to participatory regimes that respond to the demands of neoliberal governmentality.